Korea hypertension fact sheet 2018 - The Korean Society Hypertension (KSH); Hypertension Epidemiology Research Working Group; Hyeon Chang Kim; Myeong-Chan Cho (BMC, 2018)
Abstract Background The Korea Hypertension Fact Sheet 2018 aims to overview the magnitude and management status of hypertension, and their trends in Korea. Methods The Hypertension Epidemiology Research Group analyzed the 1998-2016 Korea National Health and Nutrition Examination Survey data and the 2002-2016 Korea National Health Insurance Big Data. Results The population average of systolic/diastolic blood pressure was 118/77 mmHg among Korean adults (age 30+) in 2016, showing little change in recent 10 years. However, the number of people with hypertension increased steadily, exceeding 11 million. The number of people diagnosed with hypertension increased from 3 million in 2002 to 8.9 million in 2016. The number of people using antihypertensive medication increased from 2.5 million in 2002 to 8.2 million in 2016. However, only 5.7 million people are being treated constantly. Hypertension awareness, treatment, and control rates increased fast until 2007, but showed a plateau thereafter. More than half of the young hypertensive patients (30-49 years) did not know about and treat for their hypertension. Among patients prescribed antihypertensive medications, 45% was elderly people over the age of 65 years, 57% used anti-diabetic or cholesterol-lowering medications, and 60% were prescribed two or more class of antihypertensive medications simultaneously. Conclusions In Korea, the level of hypertension management has considerably improved over the last 20 years. In order to achieve further improvement in hypertension management status, we need to find the vulnerable subgroups and develop subgroup-specific intervention strategies. It is also becoming more important to manage hypertensive patients at older age and those with concurrent chronic diseases.